2023
DOI: 10.3390/nu15061448
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Tea Consumption Increases the Incidence of Metabolic Syndrome in Middle-Aged and Older Individuals

Abstract: In middle-aged and elderly individuals, the relationship between tea consumption and incident metabolic syndrome (MetS) is still unclear. Therefore, this study intends to figure out the relationship between tea-drinking frequency and MetS in rural middle-aged and older Chinese residents. In the Northeast China Rural Cardiovascular Health Study, 3632 middle-aged or older individuals (mean age 57 ± 8, 55.2% men) without MetS were included at baseline during 2012–2013 and were followed up on between 2015–2017. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…Besides the benefits to physical function, many studies reported that tea consumption was also associated with a lower risk of diseases such as cancer, diabetes, arthritis, cardiovascular disease (CVD), stroke, genital warts, and obesity [ 50 , 51 , 52 ]. Although there are controversies regarding the benefits and risks of tea consumption, the health-promoting benefits of tea outweigh its few reported toxic effects [ 50 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the benefits to physical function, many studies reported that tea consumption was also associated with a lower risk of diseases such as cancer, diabetes, arthritis, cardiovascular disease (CVD), stroke, genital warts, and obesity [ 50 , 51 , 52 ]. Although there are controversies regarding the benefits and risks of tea consumption, the health-promoting benefits of tea outweigh its few reported toxic effects [ 50 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey did not collect such data, so it was not analyzed. Fourth, this study might also be subject to immortal time bias [ 53 ] and the healthy worker effect, as only individuals alive had the opportunity to continue drinking herbal tea or tea. Similarly, the presence of current or former smokers and alcohol drinkers in the study showing lower rates of ADL disability could also be attributed to the immortal time bias.…”
Section: Discussionmentioning
confidence: 99%